2022
DOI: 10.3390/atmos13121948
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Regional Temperature Prediction Based on Deep Spatial and Temporal Networks

Abstract: Accurate prediction of air temperature is of great significance to outdoor activities and daily life. However, it is important and more challenging to predict air temperature in complex terrain areas because of prevailing mountain and valley winds and variable wind directions. The main innovation of this paper is to propose a regional temperature prediction method based on deep spatiotemporal networks, designing a spatiotemporal information processing module to align temperature data with regional grid points … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…Therefore, the Henk de Kluijver traffic noise model is more effective in calcu-of IDW interpolation. Not like IDW, the correlation of observed points is considered in Kriging interpolation (Wu et al, 2022). The semi-variance of observed points is mapped in the 2D coordinate system, and the model is fitted for the semi-variance.…”
Section: Road Traffic Noise Visualisationmentioning
confidence: 99%
“…Therefore, the Henk de Kluijver traffic noise model is more effective in calcu-of IDW interpolation. Not like IDW, the correlation of observed points is considered in Kriging interpolation (Wu et al, 2022). The semi-variance of observed points is mapped in the 2D coordinate system, and the model is fitted for the semi-variance.…”
Section: Road Traffic Noise Visualisationmentioning
confidence: 99%
“…The ST-Net model (deep spatial and temporal network) was used to predict the future 1 hour air temperature at Baihetan Hydropower Station, China. The experimental results showed that the R 2 , RMSE, and MAE of ST-Net were 0.98, 0.63, and 0.45, respectively (Wu et al, 2022). The ANN was trained by 90% of the monthly land surface air temperatures from ERA5 and validated with the remaining 10%.…”
Section: Projection Of Future Climate Change Between 2030 and 2040mentioning
confidence: 99%
“…The numerical methods utilize physics and mathematics by formulating the equations to forecast [5]. They focus on many parameters and complex equation operations and need several engineering calculations to extract evolution trends [6]. In addition to their complexity, these methods demand great computational time and effort [7], and their accuracy is highly dependent on the spatial domain [6,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…They focus on many parameters and complex equation operations and need several engineering calculations to extract evolution trends [6]. In addition to their complexity, these methods demand great computational time and effort [7], and their accuracy is highly dependent on the spatial domain [6,8,9]. The latest studies have increasingly applied data-driven approaches.…”
Section: Introductionmentioning
confidence: 99%